2017
DOI: 10.18087/cardio.2017.7.10004
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Therapy in the Outpatient Setting: the Ability to Identify and Assess the Effectiveness of Therapy

Abstract: Резюме Цель исследования. Оценка приверженности к терапии и определение роли различных факторов, влияющих на приверженность пациентов к лечению в амбулаторных условиях, а также оценка клинической эффективности антагониста кальция фелодипина. Материалы и методы. Обследовали 5474 пациентов (мужчины и женщины) старше 18 лет с исходным уровнем офисного систолического артериального давления (АД) 140-179 мм рт. ст. и диастолического АД до 100 мм рт. ст. на фоне гипотензивной терапии или без нее, побывавших на приеме… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
(28 reference statements)
0
3
0
8
Order By: Relevance
“…The status of additional medication maintenance provided no better adherence. The study by Fofanova et al (2017) revealed no association either between the additional medication maintenance status and adherence in outpatients with arterial hypertension and CAD.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The status of additional medication maintenance provided no better adherence. The study by Fofanova et al (2017) revealed no association either between the additional medication maintenance status and adherence in outpatients with arterial hypertension and CAD.…”
Section: Resultsmentioning
confidence: 80%
“…According to that data, 61.1% of patients had poor medication adherence (≤ 3 points by 4-item Morisky scale). Yet, the target population was younger, and prevalence of CAD was less than 50% (Fofanova et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Only 40% of patients were adherent to treatment (Lukina et al 2018). Another study in patients with hypertension and SCAD examined in outpatient healthcare facilities of Moscow reported the level of non-adherence (3 points or less by 4-item MMAS) to prescribed drug therapies being at 61% (Fofanova et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Считается, что одним из важных моментов, усиливающих приверженность пациентов к терапии, является самоконтроль АД. Результаты российских исследований также доказывают, что регулярный самоконтроль АД в домашних условиях значительно повышает приверженность пациентов к лечению [8], по результатам скрининга МММ19 в России лишь треть пациентов высокого риска измеряли АД в течение последних 12 мес. Более склонны к регулярному приему гипотензивных средств пациенты с осложненной АГ, особенно имеющие в анамнезе ССО, что соответствует полученным нами данным.…”
Section: таблицаunclassified